2021
DOI: 10.1016/j.heliyon.2021.e06748
|View full text |Cite
|
Sign up to set email alerts
|

Improving the quality of used frying niger seed oil with adsorbent treatment

Abstract: High temperature continuous deep fat frying of foods will result in the frying oil and food quality deterioration. Although the quality can be retained by using fresh oil, this approach will increase the production cost. In this study, quality improvement of used niger seed oil using adsorbent treatment was evaluated. Each adsorbent was mixed with 20 h used niger seed oil (15% w/v) at 150 °C and stirred for 30 min. The oil was recovered through centrifugation at 4200 rpm for 15 min. The tested chemical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…The unprocessed NSO exhibited viscosity of 51.13 mPa s (Table 1). The prior research by Nuru and Getachew (2021) documented higher viscosity (54.50 mPa s) for fresh NSO from Ethiopia. The degree of unsaturation, density, molecular weight, and melting point influences viscosity of edible oils (Kaur et al., 2021).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The unprocessed NSO exhibited viscosity of 51.13 mPa s (Table 1). The prior research by Nuru and Getachew (2021) documented higher viscosity (54.50 mPa s) for fresh NSO from Ethiopia. The degree of unsaturation, density, molecular weight, and melting point influences viscosity of edible oils (Kaur et al., 2021).…”
Section: Resultsmentioning
confidence: 81%
“…The unprocessed NSO displayed AV of 0.48 mg KOH/g, p ‐AV of 0.17 and PV of 2.97 meq O 2 /kg (Table 1). Bhatnagar and Gopala Krishna (2014) reported lower PV (2.2 meq O 2 /kg) while Nuru and Getachew (2021) reported a relatively higher AV (2.24 mg KOH/g) for cold pressed NSO of Indian and Ethiopian origin, respectively. The IRH influenced the AV, p‐ AV, and PV of NSO.…”
Section: Resultsmentioning
confidence: 99%
“…Iodine values (IVs), peroxide values (POVs) and acid values (AVs) are often used as the indicators for the oxidative stability of fats and oils [ 17 , 22 ]. They are becoming significance for the assessment of quality and stability of oils [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…p-AV of oil was 21.8 mmol/kg at 40°C, it declined to 19.7 mmol/kg at 80°C. The literature reported a decrease in oxidation products of UO after adsorbent treatment (Bhattacharya et al, 2008;Ismail & Ali, 2015;Ismail et al, 2017;Lin et al, 2001;Nuru & Getachew, 2021).…”
Section: Purification Ofmentioning
confidence: 99%
“…Similarly, Maskan and Bağcı (2003) utilized commercial magnesium silicate (florosil), activated charcoal, bentonite, natural earth (pekmez earth) as adsorbents for the purification of the UO. Nuru and Getachew (2021) reported that FFAs and peroxide value of UO were decreased after treatment with 15% (w/v) ash, bentonite, bleaching earth, silica gel, and magnesium oxide (MgO) at 150°C for 20 hr. Moreover, a blend of MgO and ash (1:1) improved the physicochemical properties of the frying oil to a point, which is close to fresh quality.…”
mentioning
confidence: 99%